Prediction of Physical and Mechanical Properties of Al2O3–TiB2–TiC Composites Using Design of Mixture Experiments - Nestor Washington Solís Pinargote; Yuri Pristinskiy; Yaroslav Meleshkin; Alexandra Yu. Kurmysheva; Aleksandr Mozhaev; Nikolay Lavreshin; Anton Smirnov (Ceramics)
In this study, the design of mixture experiments was used to find empirical models that could predict, for a first approximation, the relative density, flexural strength, Vickers hardness and fracture toughness of sintered composites in order to identify further areas of research in the Al2O3-TiB2-TiC ternary system. The composites were obtained by spark plasma sintering (SPS) of these mixtures at 1700 °C, 80 MPa and a dwell of 3 min. The obtained experimental results were analyzed in the statistical analysis software Minitab 17, and then, different regression models were obtained for each property. Based on the selected models, contour plots were made in the Al2O3–TiB2–TiC simplex for a visual representation of the predicted results. By combining these plots, it was possible to obtain one common zone in the Al2O3–TiB2–TiC simplex, which shows the following combination of physical and mechanical properties for sintered samples: relative densities, flexural strength, Vickers hardness, and fracture toughness of than 99%, 500 MPa, 18 GPa, and 7.0 МPa·m1/2, respectively. For a first approximation in determining the further area of research, the obtained models describe well the behavior of the studied properties. The results of the analysis showed that the design of mixture experiments allows us to identify the most promising compositions in terms of mechanical properties without resorting to labor-intensive and financially expensive full-scale experiments. Our work shows that 10 different compositions were required for preliminary analysis.